2006
DOI: 10.1080/13854040500287749
|View full text |Cite
|
Sign up to set email alerts
|

The Henry-Heilbronner Index: A 15-Item Empirically Derived MMPI-2 Subscale for Identifying Probable Malingering in Personal Injury Litigants and Disability Claimants

Abstract: A new 15-item MMPI-2 subscale, the Henry-Heilbronner Index (HHI), representing a "pseudosomatic factor," was empirically derived from both the 43-item Lees-Haley Fake Bad Scale (FBS) and the 17-item Shaw and Matthews' Pseudoneurologic Scale (PNS). The HHI was superior to both the FBS and PNS in identification of symptom exaggeration in personal injury litigants and disability claimants compared to non-litigating head-injured controls. Logistic regression analyses revealed that a cutscore of > or = 8 on the HHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…A recent study found it more sensitive to memory complaints than other MMPI-2 response bias scales, yet uncorrelated with actual memory performance on the California Verbal Learning Test . Henry et al (2006) developed a 15-item scale designed to be highly sensitive and specific to somatic malingering-the exaggeration or feigning of somatic problems frequently found among personal injury claimants (Lees-Haley 1997a, b) and former Pacific theater POWs (Goldstein et al 1987). Whitney et al (2008) found the RBS and Henry-Heilbronner Index (HHI) the best MMPI-2 scales for predicting TOMM failure and found FBS relatively ineffective, in contrast to other studies.…”
Section: Self-report Inventories and Structured Interviewsmentioning
confidence: 99%
“…A recent study found it more sensitive to memory complaints than other MMPI-2 response bias scales, yet uncorrelated with actual memory performance on the California Verbal Learning Test . Henry et al (2006) developed a 15-item scale designed to be highly sensitive and specific to somatic malingering-the exaggeration or feigning of somatic problems frequently found among personal injury claimants (Lees-Haley 1997a, b) and former Pacific theater POWs (Goldstein et al 1987). Whitney et al (2008) found the RBS and Henry-Heilbronner Index (HHI) the best MMPI-2 scales for predicting TOMM failure and found FBS relatively ineffective, in contrast to other studies.…”
Section: Self-report Inventories and Structured Interviewsmentioning
confidence: 99%
“…More recently research employing a known groups design with PI litigants and disability claimants (Henry, Heilbronner, Mittenberg, & Enders, 2006) empirically derived a new scale, the 15-item Henry-Heilbronner Index (HHI), which was proposed to represent a ''pseudosomatic factor.'' The HHI is comprised of nine items from the FBS, four items from the Shaw and Mathews Pseudoneurologic Scale (PNS; Shaw & Matthews, 1965), and two items that are found on both the 920 GEORGE K. HENRY ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of PTSD, Rubenzer (2009) emphasized the MMPI-2 and the SIRS, as well as other tests. Rubenzer added that the newer MMPI-2 respondent validity check scales, such as the Response Bias Scale (RBS; Gervais et al 2007Gervais et al , 2008Gervais et al , 2009aWygant et al 2010) and the Henry Heilbronner Index (HHI;Henry et al 2006), hold great promise, as does the MMPI-2 RF (Ben-Porath and Tellegen 2008) and its revised respondent validity scales (Gervais et al 2009a, b). For example, Thomas and Locke (2010) reported a study confirming the strong psychometric properties of the Somatic Complaints Scale (RC1) of the MMPI-2 RF in patients with epilepsy and those with psychogenic nonepileptic seizures.…”
Section: Practice Commentmentioning
confidence: 99%